The Influence of Competency, Motivation and Work Discipline on the Performance of Asn ATR/BPN - Agus Salim HR; Asriati Asriati; Haeruddin Haeruddin (Jurnal Ilmu Manajemen Profitability, 2024)
This study aims to determine the effect of competence, motivation and work discipline on the performance of the State Civil Apparatus, Agrarian Spatial Planning / National Defense Agency of the City of Pinrang Regency. This type of research is a post-facto research that is correlational with a survey approach. This method is used to find out and dig deeper into the influence of the variables of Competence, motivation and work discipline on the State Civil Apparatus, Agrarian Spatial Planning / National Defense Agency of Pinrang Regency. The population in this study was the entire State Civil Apparatus, Agrarian Spatial Planning / National Defense Agency of Pinrang Regency, both Civil Servants and Non-Civil Servants totaling 68 people. Sampling was used using a questionnaire as a primary data collection tool. The sample in this study amounted to 68 people of the State Civil Apparatus, Agrarian Spatial Planning / National Defense Agency of Pinrang Regency using a saturated sample. The collection technique used in this study was a questionnaire. The questionnaire used was a structured questionnaire in a closed form that was distributed to respondents. The results of this study indicate that the influence of competence, motivation and work discipline on the performance of the State Civil Apparatus, Agrarian Spatial Planning / National Defense Agency of the City of Pinrang has a very significant influence. With an R square value of 0.765 or 76.5% which means competence, motivation and work discipline have a positive impact on the performance of the State Civil Apparatus, Agrarian Spatial Planning / National Defense Agency of Pinrang Regency.